2006
DOI: 10.1017/s0047279406000109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Attitudes Towards the Welfare State: Students' Views in Eight Democracies

Abstract: We explore the dimensionality of attitudes towards the welfare state among university students in eight countries representing four worlds of welfare: liberal, radical, conservative and social democratic. We use new data from cross-nationally comparable 25-item questionnaires to derive a two-level bi-factorial hierarchical model that specifies six different attitude facets. These facets are clustered into two distinct sets of attitudes: the 'market-based frame', which entails (a) individualism, (b) work ethic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…13 We explicitly distinguish between these two dimensions of work-welfare views because preliminary analysis revealed that the variation in the data was not adequately described by a single, latent work-welfare attitude. Moreover, this distinction is consistent with Sabbagh and Vanhuysse's (2006) results which also suggest that preferences for egalitarian redistribution can be differentiated from beliefs about the source of social inequality.…”
Section: The Econometric Modelsupporting
confidence: 87%
See 3 more Smart Citations
“…13 We explicitly distinguish between these two dimensions of work-welfare views because preliminary analysis revealed that the variation in the data was not adequately described by a single, latent work-welfare attitude. Moreover, this distinction is consistent with Sabbagh and Vanhuysse's (2006) results which also suggest that preferences for egalitarian redistribution can be differentiated from beliefs about the source of social inequality.…”
Section: The Econometric Modelsupporting
confidence: 87%
“…9 Specifically, Sabbagh and Vanhuysse (2006) argue that attitudes towards the welfare state can be understood in the context of two competing ideological frameworks; one based on markets and the other based on a welfare state. The market-based perspective is associated with a strong work ethic, a focus on individual responsibility, and a view that social inequality is driven primarily by individuals' actions.…”
Section: Work-welfare Attitudes and Welfare Historymentioning
confidence: 99%
See 2 more Smart Citations
“…And while the fiscal pressures to reduce welfare spending are strong, public support for welfare programmes remains high (e.g. Boeri et al 2001;Sabbagh and Vanhuysse 2006;Svallfors 2003). Efforts to scale down the welfare state would therefore seem to involve a high risk of electoral punishment.…”
Section: Markus Tepe and Pieter Vanhuyssementioning
confidence: 99%